ln problem - # 3

\(\displaystyle 2\ln(2) + 2\ln(3) = ?\)
Not sure what you are asking. You can simply use a calculator to get a close answer. If you want to simplify (then you should ask that!) then 2ln(2) + 2ln(3) = 2[ln(2) + ln(3)] = 2[ln(6)] = ln(36).
You really need to learn you log rules.
 
\(\displaystyle 2\ln(2) + 2\ln(3) = 2[\ln(2) * \ln(3)] = 2\ln 6\) using log rules

Is \(\displaystyle 2\ln(6)\) right or \(\displaystyle 2\ln(36)\) Where did the 36, the previous poster put up come from?
 
Last edited:
\(\displaystyle 2\ln(2) + 2\ln(3) = 2[\ln(2) * \ln(3)] = 2\ln 6\) using log rules

Is \(\displaystyle 2\ln(6)\) right or \(\displaystyle 2\ln(36)\) Where did the 36, the previous poster put up come from?

\(\displaystyle 2\ln(2) + 2\ln(3) = 2[\ln(2) * \ln(3)] = 2\ln 6 = ln(6^2) = ln(36)\)

Jason, you must not forsake your knowledge of Algebra.
 
Top